PENGARUH STRATEGI PEMBELAJARAN BERMEDIA VIDEO TUTORIAL DAN KREATIVITAS SISWA TERHADAP HASIL BELAJAR KETERAMPILAN EDITING VIDEO - Hari Setiawan; Iffah Budiningsih (Akademika : Jurnal Teknologi Pendidikan, 2015)
The study was based on the problems experienced by teachers in learning videoediting skills in vocational competence broadcasting techniques. Issues under study range inquestion: